miRVIT: A Novel miRNA Database and Its Application to Uncover Vitis Responses to Flavescence dorée Infection - Chitarra, Walter; Pagliarani, Chiara; Abbà, Simona; Boccacci, Paolo; Birello, Giancarlo; Rossi, Marika; Palmano, Sabrina; Marzachì, Cristina; Perrone, Irene; Gambino, Giorgio (Frontiers in Plant Science, 2018)
Micro(mi)RNAs play crucial roles in plant developmental processes and in defence responses to biotic and abiotic stresses. In the last years, many works on small RNAs in grapevine (Vitis spp.) were published, and several conserved and putative novel grapevine-specific miRNAs were identified. In order to reorganise the high quantity of available data, we produced ‘miRVIT’, the first database of all novel grapevine miRNA candidates characterised so far, and still not deposited in miRBase. To this aim, each miRNA accession was renamed, repositioned in the last version of the grapevine genome and compared with all the novel and conserved miRNAs detected in grapevine. Conserved and novel miRNAs catalogued in miRVIT were then used for analyzing Vitis vinifera plants infected by Flavescence dorée (FD), one of the most severe phytoplasma diseases affecting grapevine. The analysis of small RNAs from healthy, recovered (plants showing spontaneous and stable remission of symptoms) and FD-infected ‘Barbera’ grapevines showed that FD altered the expression profiles of several miRNAs, including those involved in cell development and photosynthesis, jasmonate signalling and disease resistance response. The application of miRVIT in a biological context confirmed the effectiveness of the followed approach, especially for the identification of novel miRNA candidates in grapevine. miRVIT database is available at http://mirvit.ipsp.cnr.it.